Intracranial Pressure Is a Determinant of Sympathetic Activity - Schmidt, Eric A.; Despas, Fabien; Pavy-Le Traon, Anne; Czosnyka, Zofia; Pickard, John D.; Rahmouni, Kamal; Pathak, Atul; Senard, Jean M. (Frontiers in Physiology, 2018)
Intracranial pressure (ICP) is the pressure within the cranium. ICP rise compresses brain vessels and reduces cerebral blood delivery. Massive ICP rise leads to cerebral ischemia, but it is also known to produce hypertension, bradycardia and respiratory irregularities due to a sympatho-adrenal mechanism termed Cushing response. One still unresolved question is whether the Cushing response is a non-synaptic acute brainstem ischemic mechanism or part of a larger physiological reflex for arterial blood pressure control and homeostasis regulation. We hypothesize that changes in ICP modulates sympathetic activity. Thus modest ICP increase and decrease were achieved in mice and patients with respectively intra-ventricular and lumbar fluid infusion. Sympathetic activity was gauged directly by recording renal sympathetic nerve activity in mice, muscle sympathetic nerve activity in patients, and gauged indirectly in both species by heart-rate variability analysis. In mice (n=15), renal sympathetic activity increased from 29.9 ± 4.0 bursts.sec-1 (baseline ICP 6.6 ± 0.7 mmHg) to 45.7 ± 6.4 bursts.sec-1 (plateau ICP 38.6 ± 1.0 mmHg) and decreased to 34.8 ± 5.6 bursts.sec-1 (post-infusion ICP 9.1 ± 0.8 mmHg). In patients (n=10), muscle sympathetic activity increased from 51.2 ± 2.5 bursts.min-1 (baseline ICP 8.3 ± 1.0 mmHg) to 66.7 ± 2.9 bursts.min-1 (plateau ICP 25 ± 0.3 mmHg) and decreased to 58.8 ± 2.6 bursts.min-1 (post-infusion ICP 14.8 ± 0.9 mmHg). In patients 7 mmHg ICP rise significantly increases sympathetic activity by 17%. Heart-rate variability analysis demonstrated a significant vagal withdrawal during the ICP rise, in accordance with the MNSA and RSNA findings. Mice and human results are alike. We demonstrate in animal and human that ICP is a reversible determinant of efferent sympathetic outflow, even at relatively low ICP levels. ICP is a biophysical stress related to the forces within the brain. But ICP has also to be considered as a physiological stressor, driving sympathetic activity. The results suggest a novel physiological ICP-mediated sympathetic modulation circuit and the existence of a possible intracranial (i.e. central) baroreflex. Modest ICP rise might participate to the pathophysiology of cardio-metabolic homeostasis imbalance with sympathetic over-activity, and to the pathogenesis of sympathetically-driven diseases.